Modification of Acetyl Acetone with Methyl Acrylate - Asemave, kaana; Ahile, U. J. (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Acetyl acetone was modified by a KF/alumina mediated Michael addition reaction under solventless condition with methyl acrylate. Methyl acrylate formed single and double addition with the acetyl acetone. The optimal temperature for this reaction was 393 K. The modified Î²-diketones were confirmed using GC-FID and GC-MS. The products could be tested as metal chelating agents and in related applications.